A Neighboring Aromatic-Aromatic Amino Acid Combination Governs Activity Divergence between Tomato Phytoene Synthases. Issue 4 (20th June 2019) - Cao, Hongbo; Luo, Hongmei; Yuan, Hui; Eissa, Mohamed A.; Thannhauser, Theodore W.; Welsch, Ralf; Hao, Yu-Jin; Cheng, Lailiang; Li, Li
Abstract : A lack of neighboring aromatic-aromatic amino acid combination in one of the PSY core structures is responsible for the weak carotenogenic activity of tomato fruit-specific PSY1. Abstract: Carotenoids exert multifaceted roles to plants and are critically important to humans. Phytoene synthase (PSY) is a major rate-limiting enzyme in the carotenoid biosynthetic pathway. PSY in plants is normally found as a small enzyme family with up to three members. However, knowledge of PSY isoforms in relation to their respective enzyme activities and amino acid residues that are important for PSY activity is limited. In this study, we focused on two tomato ( Solanum lycopersicum ) PSY isoforms, PSY1 and PSY2, and investigated their abilities to catalyze carotenogenesis via heterologous expression in transgenic Arabidopsis ( Arabidopsis thaliana ) and bacterial systems. We found that the fruit-specific PSY1 was less effective in promoting carotenoid biosynthesis than the green tissue–specific PSY2. Examination of the PSY proteins by site-directed mutagenesis analysis and three-dimensional structure modeling revealed two key amino acid residues responsible for this activity difference and identified a neighboring aromatic-aromatic combination in one of the PSY core structures as being crucial for high PSY activity. Remarkably, this neighboring aromatic-aromatic combination is evolutionarily conserved among land plant PSYs except PSY1 of tomato and potato ( Solanum tuberosum ). Strong transcription of tomato PSY1 likely evolved as compensation for its weak enzyme activity to allow for the massive carotenoid biosynthesis in ripe fruit. This study provides insights into the functional divergence of PSY isoforms and highlights the potential to rationally design PSY for the effective development of carotenoid-enriched crops.